Bytes of the yoke the postcolonial context of computer-mediated communication use in the Philippines - Diaz, Maria Angeli Rey Hipolito (ProQuest Information and Learning Company, 2004)
Postcolonial theory posits that former colonial and present postcolonial relations between the Philippines and the United States influence contexts of computer-mediated communication (CMC) use. Beginning from the Spanish and American colonial and postcolonial history of the country as the macrocontext of CMC use, this study examines: (a) the information and communication technology milieu in the Philippines and the Philippine-American relations in this area and (b) Filipino organizational conditions surrounding the use of CMC to protect coral reefs in the Philippines with the help of an American organization. This study aims to show how the colonial and postcolonial relations between the Philippines and the United States are interrelated with Philippine-American relations in the area of information and communication technology and with the personal lived experiences of Filipino organizational members who use CMC to support a Philippine-American inter-organizational relationship. The emphasis on multifaceted contexts is based on the premise that context should not be thought of as a passive, unidimensional backdrop but rather as a dynamic process that aggressively routes organizational communication into specific directions. Findings indicate that the three contexts collectively create complex contradictions where the simultaneous and paradoxical enabling and constraining of Filipino organizational communication strategies inversely lead to either the facilitation or disruption of American technological colonization. While these findings support postcolonial theory's position that past colonial realities persist in postcolonial life, these findings also reveal postcolonial theory's inability to explain completely organizational communication processes that require the mediation of tightly coupled technological tools. This deficiency suggests the need to extend postcolonial theory's frames to include the material conditions and lived experiences of postcolonials in theorizing about computer-mediated communication and its use in postcolonial societies and about the persistence of the colonial past into the postcolonial present.--Abstract.